Dynamika wartości marketingowej - Strużycki, Marian (The Dynamics of the Marketing Value, 2006)
The author discusses the premises and emphasizes the need for the creative discussion about present and future dilemmas of marketing. He points to the following directions of changes and new orientations: the business-market orientation, the orientation on values referred to the entire firm, the regional-local orientation, the subjective-trade orientation, the orientation of a law suit, the institutional-problem orientation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 9-14